Eliosin-an alternative product from the HmPKD1 locus is a component of endoplasmic reticulum mitochondria membrane contact sites - Almira Kurbegovic; Virginie Lazar; Wei-Min Xu; Maya Seshan; John S. Underwood; Radmila Micanovic; Jeremy M. Pomerantz; Rajneesh Srivastava; Sarath Janga; Emma H. Doud; Sherry Clendenon; Marie Trudel; et al. (PLoS ONE, 2025)
The human PKD1 gene locus region is the site that when mutated, causes 87% of the cases of human autosomal dominant polycystic kidney disease (ADPKD). This gene generates a full-length 14 kb message and encodes polycystin-1 (PC1). Informatic analysis of the PKD1 locus reveals 38 additional transcripts in the database, the most abundant cDNA is TESTI2047494 (GenBank ACC. No. DB056008) that maps to the 3’ region with active and open chromatin. This PKD1 locus region in human adult kidney cDNA probed by several sets of primers and sequencing produces an alternative transcript with a transcriptional start site in intron 40 that undergoes exon 42 skipping but aligns with exon 43−46 conventional splicing of the H mPKD1 gene. To assess the broader significance of this transcript, transcriptional characterization uncovered a highly similar murine renal alternative transcript suggesting a conserved functional role. The human alternative cDNA was analyzed for protein expression and only one of three reading frames led to a 47 kDa protein that is given the name Eliosin. Eliosin protein initiates from a non-canonical translation start site Leucine in exon 41 that generates 5 unique amino-terminal amino acids in a different frame from PKD1 . In 2D-gel analysis, Eliosin protein detected by anti-C terminal PC1 antibodies has a pI of 9.0 and the relative molecular weight was confirmed. Eliosin co-localizes with mitofusin-1, IP3R and dynamin related protein-1 (DRP1), proteins associated with ER mitochondria membrane contact sites (ERMCS). Eliosin observed in cotransfection studies with DRP1 support sequestration and/or competition mechanism at the ERMCS from classical interaction. Strikingly, exogenous Eliosin in immortalized ADPKD renal epithelial cells converts fragmented mitochondria populations to a filamentous shape. Our studies highlight the genomic complexity of the locus, a newly identified transcript and ERMCS protein, Eliosin with a role in mitochondria dynamics and potential impact in ADPKD progression.